The Impact of Fraud and Corruption on the Effectiveness of Customs Duties Collection: case of Zimbabwe Revenue Authority - Tiriboyi, Cosmas (Midlands State University, 2017)
The Zimbabwe Revenue Authority has been suffering from fraud and corruption challenges due to inadequate controls, discretional interface, lack of accountability and the network of accomplices. It is against this background that the study seeks to investigate the impact of fraud and corruption on the effectiveness of custom duties collection with specific emphasis on the relationship between fraud and revenue. The objectives of this study were to identify the causes of fraud and corruption, assessing the risk of material misstatements of revenue due to fraud and to determine the ant-fraud strategies, their effectiveness and the relationship between fraud, corruption and revenue. Both primary and secondary sources of data were made use of with the questionnaires and interviews standing out as the research instruments to gather the data. Time series data for the period of January 2009 to January 2014 was regressed using a multi-regression technique the Ordinary Least Squares method (OLS). The e-views 4 software was adopted to make all the necessary estimations. Literature from various scholars who investigated the causes and impact of fraud and corruption on revenue collection was reviewed. The study indicates that there is a negative relationship between fraud and revenue collected. The study concluded and recommended to organisations that they should develop anti-fraud framework policies, automate operations and integrate application systems to reduce human intervention than when processing is manual and also ZIMRA should also protect witnesses and whistle-blowers by establishing confidential communication channels to relay information pertaining to fraud and corruption.